Inhibitory Effects of the Flower of Canadian Goldenrod (Solidago altissima L.) on Tumour Promotion Induced by 12-O-tetradecanoylphorbol-13-actete - Yasukawa, Ken (Journal of Nutritional Therapeutics, 2015)
Cancer prevention is an important issue in various healthcare fields; thus, we continue searching for potential useful compounds. This study focuses on the utilization of Canadian goldenrod, which is commonly seen growing on vacant land. Methanol extracts of the flower of Canadian goldenrod inhibited inflammation by 12-O-tetradecanoylphorbol-13-acetate (TPA) and inhibited promotion in the mouse skin two-stage carcinogenesis model. Five inhibitory compounds were isolated from the active fraction, and these compounds were identified as flavonoids; kaempferol (1), quercetin (2), kaempferol-3-O-rutinoside (3), querectin-3-O-rutinoside (4), and isorhamnetin-3-O-rutinoside (5). These compounds inhibited the inflammation induced by TPA, and the inhibitory effects were similar to indomethacin.